Michel parameters in the presence of massive Dirac and Majorana neutrinos - Juan Manuel Márquez; Gabriel López Castro; Pablo Roig (Journal of High Energy Physics, 2022)
Abstract We analyse the effects of Dirac and Majorana neutrinos on leptonic decays of muon and tau leptons using the most general four-lepton effective interaction Hamiltonian of dimension six. We calculate the specific energy and angular distribution of the final charged lepton, including the polarizations of the initial and final charged leptons. We discuss the new generalized Michel parameters and focus on the effects of the heavy neutrino masses that would lead to sizable contributions on scenarios where the new sterile neutrinos have non-negligible mixing. Specifically, the most promising scenario is found for the case of τ decay with one heavy final-state neutrino with a mass around 102 − 103 MeV, where the linear term suppression could be of order 10 −4, low enough to be measured in current and forthcoming experiments.